Community Obligations and Participation in Oversight of Investigations Conducted by The Indonesian National Police - M. Rohmidhi Srikusuma; Urip Giyono (Jurnal Hukum In Concreto, 2026)
Investigation constitutes a crucial stage in the criminal justice system, as it determines the direction of law enforcement processes and has direct implications for the protection of human rights. The Indonesian National Police, as the institution vested with investigative authority, is required to perform its duties in a professional, transparent, and accountable manner, particularly following the enactment of the new national Criminal Code. In this context, public participation serves as an essential mechanism for overseeing investigative processes in order to prevent abuses of authority and to strengthen public trust in law enforcement institutions. This study aims to normatively analyze the obligations and participation of the public in overseeing investigations conducted by the Indonesian National Police, as well as to identify the forms, mechanisms, and challenges of such participation. This research employs a normative legal research method with a statutory approach and qualitative analysis of primary and secondary legal materials. The findings indicate that although constitutional and regulatory frameworks provide opportunities for public participation, mechanisms for public oversight of police investigations remain underdeveloped. Therefore, strengthening regulatory frameworks, enhancing public legal awareness, optimizing the role of external oversight institutions, and providing secure and transparent complaint mechanisms are necessary to ensure accountable and just investigative practices.